Influence of the Zn2+ concentration on the defect structure and optical properties in Zn:Fe:Cu:LiNbO3 crystals - Zhehua Yan; Li Dai; Shunxiang Yang; Zesheng Ji (AIP Advances)
Special attention has been paid to holographic storage and 3D display in recent years. LiNbO3 crystal is a distinguished multifunctional material where the field of holographic storage is of paramount importance. In this work, the Czochralski method was employed to grow a series of Zn:Fe:Cu:LiNbO3 crystals with different doping concentrations of Zn2+ ions (1, 3, 5, and 7 mol. %). The effects of doped ions of Zn2+, Fe3+, and Cu2+ on crystal lattice parameters and defect structure were characterized by XRD and inductively coupled plasma atomic emission spectrometer (ICP-AES), and the optical homogeneity was characterized by the birefringence gradient method. The x-ray powder diffraction experiments reveal that the crystal lattice structure remains unaffected by doping. The ICP-AES analysis revealed that as the concentration of Zn2+ ions increased, there was an observed enhancement in the effective segregation coefficient of Fe3+ and Cu2+ ions, while a decrease was noted in that of Zn2+ ions. The birefringent gradient method demonstrates that the optical homogeneity improves with an increasing concentration of Zn2+ ion doping and reaches its maximum when the concentration of Zn2+ ion reaches 7 mol %. For the first time, the optical uniformity of Fe:Cu:LiNbO3 crystals has been enhanced by heavy Zn2+ ion doping, making it possible to apply it in the field of holographic storage.